Reasons for Bankruptcy of Natural Persons in Lithuania - Paškevičius, Arvydas; Jurgaitytė, Neringa (Ekonomika, 2015)
In Lithuania, bankruptcy of natural persons is a relatively new subject that has been scientifically only randomly dealt with. The bill of Bankruptcy of Natural Persons in Lithuania was proposed as early as in spring 2009 (No.XIP-450, 24.03.2009). The bill met with a considerable amount of criticism and was postponed for further improvement. By decree No. 413 of April 7, 2010, the Government of the Republic of Lithuania approved the concept of the bankruptcy of natural persons of the Republic of Lithuania. The principal goal of the concept was to consolidate the main provisions of the future law. The Law of Bankruptcy of Natural Persons of the Republic of Lithuania has come into effect since March 1, 2013.The authors of the article overview the concept and models of bankruptcy of natural persons and introduce the advantages and shortcomings of the institute of bankruptcy of natural persons. Based on scientific sources of Lithuanian and foreign authors, the article offers a theoretically systemized version of the main reasons determining the bankruptcy of natural persons. The reasons fall into two categories – economic and social. The article is mainly targeted at defining the reasons that determine the bankruptcy of natural persons in Lithuania. To achieve this goal, a quantitative survey of the questionnaires of natural persons affected by bankruptcy has been taken for the basis. In their questionnaires, the natural persons affected by bankruptcy have been asked to evaluate the reasons of bankruptcy. The results have been analyzed with the help of factor analysis and statistically processed using the SPSS statistical software package.
Keywords: bankruptcy; bankruptcy of natural persons; reasons for the bankruptcy of natural persons